Cost estimation of newly developed functional processed cheese spread – An engineering approach - Giri, Apurba (Indian Journal of Dairy Science, 2018)
The study was carried out to compare the production cost of newly developed functional cheese spread where in inulin, phytosterols and ω-3 fatty was additionally incorporated with control cheese spread. The processed cheese spread was manufactured in a cheese plant with assumption of 1000 kg cheese spread production per day. Cost for land and building, plant and machinery, other fixed assets, manpower, utilities, raw material, laboratory charges, cleaning and sanitizing, maintenance and repair, interest, depreciation, insurance and taxes, advertisement, marketing and distribution etc. were calculated. It was estimated that the production cost of functional cheese spread (Rs. 36.04/100 g) was 78.73% higher as compared to control cheese spread (Rs. 20.16/ 100 g) mainly due to increase expenditure in raw material.